A serological survey of tick-borne pathogens in dogs in North America and the Caribbean as assessed by Anaplasma phagocytophilum, A. platys, Ehrlichia canis, E. chaffeensis, E. ewingii, and Borrelia burgdorferi species-specific peptides - Barbara A. Qurollo; Ramaswamy Chandrashekar; Barbara C. Hegarty; Melissa J. Beall; Brett A. Stillman; Jiayou Liu; Brendon Thatcher; Elizabeth Pultorak; Brian Cerrito; Mary Walsh; Edward B. Breitschwerdt (Infection Ecology & Epidemiology, 2014)
Introduction: Tick-borne pathogens cause a spectrum of disease manifestations in both dogs and humans. Recognizing regional and temporal shifts in exposure are important as tick distributions change. To better delineate regional exposure to canine tick-borne pathogens, an expanded set of species-specific peptides were used to detect Anaplasma phagocytophilum (Aph), Anaplasma platys (Apl), Ehrlichia canis (Ec), Ehrlichia chaffeensis (Ech), Ehrlichia ewingii (Eew), and Borrelia burgdorferi (Bb) antibodies in canine serum. Methods: Archived canine serum samples (n=6,582) collected during 2008–2010 and in 2012 from the US, Canada, and the Caribbean were retrospectively screened for antibodies against Ehrlichia and Anaplasma species-specific peptides. Overall, regional and temporal seroprevalence rates were determined. Results: Overall Bb and Eew were the most seroprevalent pathogens. During 2008–2010, seroprevalence rates increased overall for Aph and Ech, and regionally, Bb and Aph seroprevalence rates increased in the South. Canada had unexpectedly high seroprevalence rates for Ec and Apl. The most common co-exposures were Eew+Ech, followed by Aph+Bb and Eew+Bb. Conclusions: This study demonstrated significant shifts in canine vector-borne disease seroprevalence rates. The use of specific peptides facilitated improved geographic delineation of tick-borne pathogen distributions among dogs, which may enhance epidemiological surveillance of vector-borne pathogens shared by dogs and humans.